Management Inadvertent Hypothermia Perioperative : A Systematic Review - Yazid, Syahrul Abdul; Sriyono, Sriyono; Harmayetty, Harmayetty (Universitas Tribhuwana Tunggadewi, 2024)
Shivering is a common issue experienced by patients during surgery, caused by exposure to cold operating room air. This loss of body heat can make patients uncomfortable and require more oxygen. The purpose of this study is to evaluate the management of shivering and hypothermia based on literature review. A systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). The article selection process followed the PICO framework. The population consists of individual patients undergoing surgery with spinal anesthesia. The study included patients who experienced shivering and underwent non-pharmacological interventions for temperature management. Articles published between 2018 and 2024 were searched in four databases: Scopus, EBSCO, ProQuest, and PubMed. The quality of the articles was evaluated using the Joanna Briggs Institute (JBI) format. The initial search identified 270 articles, which were narrowed down to 12 after removing duplicates and reviewing titles and inclusion criteria. In this study, 1326 individuals undergoing surgery were surveyed. To prevent hypothermia and shivering, several non-pharmacological methods can be used, such as pre-warming using forced-air warming, which increases body temperature. Isothermic irrigation was found to reduce the decrease in core temperature and the incidence of shivering. Preoperative warming can be done for durations of 30, 15, and 10 minutes before induction. To conclude, shivering can be prevented by non-pharmacological methods to increase core body temperature so that it will increase patient comfort during surgery. One of the innovations that can be done is by making warm vests